Early diastolic left ventricular inflow pressures in normal subjects and patients with dilated cardiomyopathy. Reconstruction from pulsed Doppler echocardiography. - Fujimoto, S. (1995)
OBJECTIVE--To estimate early diastolic left ventricular inflow pressures in normal subjects and patients with dilated cardiomyopathy, and thus to assess the potential effect of restoring forces. METHODS--Early diastolic left ventricular inflow pressures were reconstructed using the ventricular blood as an accelerometer, by measuring velocity at 1 cm intervals within the left ventricle from mitral ring to apex by pulsed Doppler echocardiography, and differentiating the records to obtain the acceleration. Aortic component of second heart sound (A2) was used to fix relative timings. The local pressure gradient was determined from the acceleration at each level, and the total pressure drop during the acceleration (+ peak PD) and deceleration (- peak PD) phases of the filling interval were determined by summing the local increments. The total stroke volume (SV) at the left ventricular outflow tract and the mitral stroke distances (MSD) were also determined, using the time-velocity integral at mitral ring level. Effective flow orifice area was thus SV/MSD. Inflow jet width across the mitral valve was estimated by cross sectional colour Doppler flow mapping. PATIENTS--32 patients with dilated cardiomyopathy with a dominant mitral E or summation wave, and 24 normal subjects of similar ages. RESULTS--Normal + peak PD was 3.9 (SD 0.7) v 7.4 (2.2) mm Hg in dilated cardiomyopathy (P < 0.01). Normal - peak PD was 2.5 (0.9) v 5.6 (2.8) mm Hg in cardiomyopathy (P < 0.01). Normal effective flow orifice area was 5.9 (1.3) v 1.9 (0.8) [range 0.9 approximately 3.7] cm2 in cardiomyopathy (P < 0.01). This corresponded to 71 (18)% of the end systolic cavity cross section in normals v 11 (6)% in dilated cardiomyopathy (P < 0.01). Normal cross sectional colour inflow jet width was 2.7 (0.3) v 1.5 (0.4) cm in cardiomyopathy (P < 0.01). The jet width correlated with flow width calculated from effective flow orifice area (r = 0.82, P < 0.01). CONCLUSIONS--(1) Total early diastolic positive and negative peak pressure drop are normally low, so that significant negative left ventricular pressures are not needed to explain normal resting early diastolic mitral flow velocities. (2) These low pressure drops are only possible with a large effective orifice area approaching end systolic left ventricular cavity area. (3) Atrioventricular pressure drops are much greater in dilated cardiomyopathy, where increased inflow accelerations are due to reduced effective flow orifice area. These disturbances will impair filling independently of any abnormality of relaxation or compliance.